2008
DOI: 10.1007/s00439-007-0460-x
|View full text |Cite
|
Sign up to set email alerts
|

Blue eye color in humans may be caused by a perfectly associated founder mutation in a regulatory element located within the HERC2 gene inhibiting OCA2 expression

Abstract: The human eye color is a quantitative trait displaying multifactorial inheritance. Several studies have shown that the OCA2 locus is the major contributor to the human eye color variation. By linkage analysis of a large Danish family, we finemapped the blue eye color locus to a 166 Kbp region within the HERC2 gene. By association analyses, we identified two SNPs within this region that were perfectly associated with the blue and brown eye colors: rs12913832 and rs1129038. Of these, rs12913832 is located 21.152… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
271
2
42

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(334 citation statements)
references
References 26 publications
19
271
2
42
Order By: Relevance
“…This was in concordance with previous studies in which HERC2 rs12913832 was described to be the main predictor of qualitative [14,15,16] and quantitative eye colour [17]. To assess possible confounding effects of HERC2 rs12913832 on the gender effect, association tests of gender with the PIE-score were carried out using the non-parametric Wilcoxon-rank-sum test based on the SNP-types of HERC2 rs12913832 (Table 2 and Figure 1).…”
Section: Association Between Gender the Irisplex Snps And Eye Coloursupporting
confidence: 84%
“…This was in concordance with previous studies in which HERC2 rs12913832 was described to be the main predictor of qualitative [14,15,16] and quantitative eye colour [17]. To assess possible confounding effects of HERC2 rs12913832 on the gender effect, association tests of gender with the PIE-score were carried out using the non-parametric Wilcoxon-rank-sum test based on the SNP-types of HERC2 rs12913832 (Table 2 and Figure 1).…”
Section: Association Between Gender the Irisplex Snps And Eye Coloursupporting
confidence: 84%
“…All those heterozygous for the Polynesian OCA2 mutation p.Gly775Asp with green or blue eyes had known Caucasian ancestors, suggesting possible interaction with other pigmentation-influencing variants. 16,22,23 There was a predominance for gray hair in heterozygous carriers; however, the majority of participants expressed black hair irrespective of carrier status and age-related hair graying must be taken into account.…”
Section: Oca2 Gene Mutation Detectionmentioning
confidence: 99%
“…20 Polymorphism within the OCA2 gene is significantly associated with eye color 21 and also underlies the previous assignment of the brown eye (BEY2/EYCL3, MIM227220) and brown hair (HCL3, MIM601800) phenotypes. A single single-nucleotide polymorphism in the neighboring gene, HERC2, was recently found to be a common founder polymorphism affecting an OCA2 regulatory element, which in turn results in blue eye color 22,23 and reduced melanin content in cultured human melanocytes. 24 MC1R is associated with red hair in the European population and has been found to modify the OCA2 phenotype to also express red hair.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies of this region and its sequence revealed that a change in one nucleotide, single-nucleotide polymorphism (SNP), regulates the binding site for the transcription of the OCA2 gene, altering its expression. 9 The base changes from a thymine to a cytosine. The SNP, rs12913832, causes a phenotype change from brown to blue eyes, respectively.…”
Section: Genotype-phenotype Interactionsmentioning
confidence: 99%
“…These genes are of the greatest importance for eye color. [9][10][11] Numerous ubiquitin ligases are coded for throughout the body. Chromosome 15 contains HERC1 and HERC2.…”
Section: Introductionmentioning
confidence: 99%